2015
DOI: 10.1111/gean.12093
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Rapidity of Change in Complex Urban Systems: A Multidimensional, Local‐Scale Approach

Abstract: This study illustrates an exploratory approach based on a Multiway Factor Analysis (MFA) to estimate rapidity of change in complex urban systems, based on “fast” and “slow” variables. The proposed methodology was applied to 18 socioeconomic indicators of long‐term (1960–2010) transformations in 115 municipalities of Athens’ metropolitan area (Greece), including demography, land‐use/planning, and urban form and functions. Athens was regarded as a dynamic urban area with diversified structures and functions at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
165
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 157 publications
(169 citation statements)
references
References 56 publications
3
165
0
1
Order By: Relevance
“…At the same time, migration can aggravate labour market imbalances in the short term, amplifying temporarily the geographical dispersion of unskilled workers' wages (Devillanova, 2004). The extent of regional variation in population dynamics revealed by our analysis and earlier reports (Fuguitt & Beale, 1996) indicates how differences in physiography, settlements, and economy are reflected in demographic dynamics (Salvati & Serra, 2016), which are obscured when larger regional groupings (or national-scale data) are used.…”
Section: Discussionmentioning
confidence: 63%
“…At the same time, migration can aggravate labour market imbalances in the short term, amplifying temporarily the geographical dispersion of unskilled workers' wages (Devillanova, 2004). The extent of regional variation in population dynamics revealed by our analysis and earlier reports (Fuguitt & Beale, 1996) indicates how differences in physiography, settlements, and economy are reflected in demographic dynamics (Salvati & Serra, 2016), which are obscured when larger regional groupings (or national-scale data) are used.…”
Section: Discussionmentioning
confidence: 63%
“…Trends over time in some indicators guided by the second demographic transition (e.g., fertility rates) have rarely been associated with heterogeneous spatial dynamics that depend on suburbanisation (Kabisch & Haase, ) and, more recently, on the short‐term impact of the economic crisis. With this perspective in mind, empirical evidence from our study indicates a particularly complex territorial patchwork that can be better interpreted using a multivariate exploratory spatial analysis (Carlucci et al, ), because different analysis' dimensions are usually identified with the use of multidimensional techniques (Salvati & Serra, ). The analysis carried out in the present study discriminates population dynamics along the urban–rural gradient from demographic processes oriented along a more subtle social gradient on the basis of territorial gaps in disposable income, class segregation, and concentration of economic activities, corresponding to the east–west axis in Athens.…”
Section: Discussionmentioning
confidence: 96%
“…dimensions are usually identified with the use of multidimensional techniques (Salvati & Serra, 2016). The analysis carried out in the present study discriminates population dynamics along the urban-rural gradient from demographic processes oriented along a more subtle social gradient on the basis of territorial gaps in disposable income, class segregation, and concentration of economic activities, corresponding to the east-west axis in Athens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider the 30 municipalities of the valley as units of analysis because they constitute the smallest unit of governance and management in the Madrid region and also the most detailed level at which LULC and socio-economic census data are available [24], [25]. The data matrices analysed, (m x d L ) and (m x d S ), contained the set of municipalities described over time by means of 46 LULC and 27 socioeconomic descriptors, respectively.…”
Section: Socio-ecological Analysismentioning
confidence: 99%